A traumatic fracture in a giant Eocene penguin from Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; Pérez, Leandro Martín; Acosta, Walter; Reguero, Marcelo Alfredo (Antarctic Science)
A fractured femur of a giant fossil penguin from the Anthropornis nordenskjoeldi Biozone (Late Eocene), Isla Marambio (Seymour Island), Antarctica (La Meseta Formation) is described. Palaeoecological, palaeopathological and taphonomical implications derived from the analysis of the kinds of fractures identified are also discussed. The main fracture has irregular margins, indicating there was collagen in the bone at the time of the impact. In this fracture, a mineral deposit was also identified as a fracture hematoma. According to the antemortem classification of fractures, it was produced by an indirect mechanism, provocating a "butterfly wing" or "third fragment" fracture. The remaining fractures are assigned to times of biostratinomic and fossil diagenesis. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Pérez, Leandro Martín. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleozoología Invertebrados; Argentina Fil: Acosta, Walter. Universidad Nacional de La Plata. Facultad de Ciencias Veterinarias; Argentina Fil: Reguero, Marcelo Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina